Early talent identification in tennis: A retrospective study - Siener, M.; Ferrauti, A.; Hohmann, A. (International Journal of Racket Sports Science, 2021)
Talent identification often begins at the age of entry into a sport: namely, even under the age of 9 years old (U9). However, the success of such early talent identification is questionable. Therefore, the aim of this long-term retrospective study is to examine whether today`s more successful junior tennis players already differed from today`s less successful junior tennis players in terms of physical fitness and motor competence when both groups were U9. If significant differences in performance characteristics between successful and less successful tennis players were already apparent at this young age, such characteristics could be used to forecast talent at an early stage. Based on their current tennis success, a total of 174 junior tennis players were divided into national ranked players (n = 16: players who achieved a place in the official national junior tennis ranking list of the German Tennis Federation) and non-ranked players (n = 158). All of these players had already participated in two anthropometric and nine physical fitness and motor competence tests at U9 (e.g., sprint, endurance run, ball throw). Using a MANCOVA and a correlation analysis, we retrospectively examined whether the two current performance groups had differed significantly in their U9 test scores and whether these athletes` U9 test performance scores correlated with their current playing success. No significant (p < 0.05) differences were found between ranked and non-ranked junior players in terms of U9 body weight and height. However, with the exception of flexibility, all physical fitness tests and motor competence tests showed significant results. The ball throw was the most relevant test parameter, as it showed the highest prognostic validity (effect size ?2 = .157 and r = .360). This test was followed by the two test tasks standing long jump (effect size ?2 = .081 and r = .287) and endurance run (effect size ?2 = .065 and r = .296). Overall, the U9 findings are in line with the results from other studies of U12-U18 tennis players. Therefore, it can be assumed that talent-specific characteristics remain stable over a certain period of time and that U9 test performances may provide an early indication of later playing success.